Calcitonin Gene-Related Peptide (CGRP) and Migraine - Durham, Paul L. (2006)
The neuropeptide calcitonin gene-related peptide (CGRP) has long been postulated to play an integral role in the pathophysiology of migraine. While clinical findings are consistent with such a role, the specific pathogenic mechanisms of CGRP in migraine have remained speculative until recently. Through advances in molecular neuroscience, the pathogenic mechanisms of CGRP in migraine have begun to be elucidated. This paper discusses the hypothesized role of CGRP in migraine and reviews recent findings on the molecular mechanisms of this neuropeptide in migraine pathophysiology. Studies in cultured trigeminal neurons demonstrate that CGRP is released from trigeminal ganglia cells, that CGRP transcription is increased under conditions mimicking neurogenic inflammation, that migraine pharmacotherapies can both reduce CGRP release and inhibit CGRP transcription, and that tumor necrosis factor-α (TNF-α), an endogenous inflammatory mediator implicated in migraine, can stimulate CGRP transcription. Together, the results suggest that, in migraine, activation of trigeminal nerves release CGRP and other peptides that cause the release of proinflammatory mediators. These mediators further increase CGRP synthesis and release over hours to days in correspondence with the 4- to 72-hour duration of a typical migraine episode. The increased CGRP synthesis and release might be mediated by activation of mitogen-activated protein kinase pathways, which, in turn, can be modulated by endogenous inflammatory substances such as TNF-α and affected by drugs such as sumatriptan.